2022
DOI: 10.1108/jcefts-10-2021-0063
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating megaprojects from a sustainability perspective: a case of China-Pakistan economic corridor (CPEC)

Abstract: Purpose This paper aims to examine the impact of various economic, social and environmental issues on the sustainable development of Pakistan, both directly and indirectly through the sustainability dimensions of China–Pakistan Economic Corridor (CPEC), a multi-billion-dollar megaproject. Design/methodology/approach Using a quantitative (deductive) methodological approach, data were collected using a strategy of an online questionnaire survey from diverse stakeholders of CPEC in Pakistan. Partial least squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…After indicating these measures, the review and proper implementation of these actions should be reported to minimize the negative environmental impacts, i.e., CO2 emissions, biodiversity loss, agricultural land loss, and water pollution linked with the development of CPEC road project. The results of this study recommend a proper EIA of CPEC road project to ensure environmental sustainability and long-term benefits (Aslam, 2006;Hassan et al, 2022;Zhang et al, 2013).…”
Section: Gamma Testmentioning
confidence: 78%
“…After indicating these measures, the review and proper implementation of these actions should be reported to minimize the negative environmental impacts, i.e., CO2 emissions, biodiversity loss, agricultural land loss, and water pollution linked with the development of CPEC road project. The results of this study recommend a proper EIA of CPEC road project to ensure environmental sustainability and long-term benefits (Aslam, 2006;Hassan et al, 2022;Zhang et al, 2013).…”
Section: Gamma Testmentioning
confidence: 78%
“…One of the main benefits of CPEC is the potential to boost Pakistan's economy. The project is expected to generate employment opportunities and increase trade between China and Pakistan (Khan, 2019). According to a report by the International Monetary Fund (IMF), CPEC could increase Pakistan's GDP growth by 1-2 percentage points per year over the medium term (IMF, 2017).…”
Section: Economic Prospects Of Cpecmentioning
confidence: 99%
“…In addition to economic benefits, CPEC has the potential to bring social benefits to Pakistan. For example, the project includes plans for the construction of hospitals, schools, and vocational training centers (Khan, 2019). These facilities could improve access to healthcare and education for people living in remote areas of Pakistan.…”
Section: Social Benefits Of Cpecmentioning
confidence: 99%
See 2 more Smart Citations